Le ReTeHNor : un répertoire numérique de l’hagiographie latine de Normandie - Laura Vangone (Tabularia)
Researchers’ work is more and more accompanied by the practice of digital humanities which allow them to better accomplish their research and better exploit the results. Thus, these technologies have stimulated the emergence of many databases online. So, the ReTeHNor (Repertorium Textuum Hagiographicorum in Normannia conscriptorum), which collect the Latin hagiographical texts written in the area of the duchy of Normandy during the ducal period (911-1204), is one of these digital repertoire. Based on the BHL model, it collects files describing these hagiographical texts from a historical and a literary point of view and enable to have, thanks to different modes of inquiry, a critical and statistic view of the hagiography of Normandy: how many centers of hagiographic production? How many hagiographers? Which models of sanctity? Which types of hagiographic writing? Etc.